Variability of hydroxyl radical (OH) reactivity in the Landes maritime pine forest: results from the LANDEX campaign 2017 - Bsaibes, Sandy; Al Ajami, Mohamad; Mermet, Kenneth; Truong, François; Batut, Sébastien; Hecquet, Christophe; Dusanter, Sébastien; Léornadis, Thierry; Sauvage, Stéphane; Kammer, Julien; Flaud, Pierre-Marie; Perraudin, Emilie; et al. (Atmospheric chemistry and physics, 2020)
Total hydroxyl radical (OH) reactivity measurements were conducted during the LANDEX intensive field campaign in a coniferous temperate forest located in the Landes area, southwestern France, during July 2017. In order to investigate inter-canopy and intra-canopy variability, measurements were performed inside (6 m) and above the canopy level (12 m), as well as at two different locations within the canopy, using a comparative reactivity method (CRM) and a laser photolysis–laser-induced fluorescence (LP-LIF) instrument. The two techniques were intercompared at the end of the campaign by performing measurements at the same location. Volatile organic compounds were also monitored at both levels with a proton transfer time-of-flight mass spectrometer and online gas chromatography instruments to evaluate their contribution to total OH reactivity, with monoterpenes being the main reactive species emitted in this forest dominated by Pinus pinaster Aiton. Total OH reactivity varied diurnally, following the trend of biogenic volatile organic compounds (BVOCs), the emissions and concentrations of which were dependent on meteorological parameters. Average OH reactivity was around 19.2 and 16.5 s−1 inside and above the canopy, respectively. The highest levels of total OH reactivity were observed during nights with a low turbulence (u*≤0.2 m s−1), leading to lower mixing of emitted species within the canopy and thus an important vertical stratification characterized by a strong concentration gradient. Comparing the measured and the calculated OH reactivity highlighted an average missing OH reactivity of 22 % and 33 % inside and above the canopy, respectively. A day–night variability was observed on missing OH reactivity at both heights. Investigations showed that during daytime, missing OH sinks could be due to primary emissions and secondary products linked to a temperature-enhanced photochemistry. Regarding nighttime missing OH reactivity, higher levels were seen for the stable and warm night of 4–5 July, showing that these conditions could have been favorable for the accumulation of long-lived species (primary and secondary species) during the transport of the air mass from nearby forests.